The Influence of Work Family Conflict, Workload On The Female Employee Performance Surabaya Health Office With Work Stress As An Intervening Variable - Arniningtyas, Aprilina Gayuh; Sukoco, Agus (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The purpose of this research is to determine and analyze the influence of work family conflict, workload on the female employee performance Surabaya Health Office with work stress as an intervening variable. Design/methodology/approach: The data collection technique used to fill out a questionnaire using the Saturated Sampling method which was distributed to the sample population of 48 female civil servant (PNS) as respondents. 53 questionnaires were distributed and 48 questionnaires were filled and processed using the SEM-PLS application. Findings:. Finding the research results show that work family conflict there is a positive and not significant influence on female employee performance, workload there is a positive and not significant influence on female employee performance, work family conflict there is a positive and significant influence on work stress, workload there is a negative and not significant influence on work stress, work stress there is a negative and significant influence on female employee performance, work family conflict there is a negative and significant influence on female employee performance with work stress as intervening variable, and workload there is a positive and not significant influence on female employee performance with work stress as intervening variable. Paper type: Research paper